Poor poor dumb mouths, and bid them speak for me: Theorizing the use of personas in practice. Issue 2 (3rd April 2018) - Rose, Emma J.; Tenenberg, Josh
ABSTRACT: Although personas are commonly used to represent users in design, their rhetorical function has been little explored. In this article, the authors theorize personas' rhetorical function as ventriloquization, where one person speaks with the voice of another. In ventriloquizing users through personas, practitioners speak for users, while scripting personas to speak for their creators: each magnifies the others' voice. Personas represent a strategic rhetorical gambit for gaining legitimacy within organizations and technological decision-making processes.